Multi‐decadal water table manipulation alters peatland hydraulic structure and moisture retention. Issue 13 (8th January 2015) - Moore, P.A.; Morris, P.J.; Waddington, J.M.
Abstract A peatland complex disturbed by berm construction in the 1950s was used to examine the long‐term impact of water table (WT) manipulation on peatland hydraulic properties and moisture retention at three adjacent sites with increasing depth to WT (WET, INTermediate reference and DRY). Saturated hydraulic conductivity (Ks) was found to decrease with depth by several orders of magnitude over a depth of 1–1.5 m at all sites. The depth dependence of WT response to rainfall was similar across sites: WT response increased from 1 : 1 at the surface, to 5 : 1 at 50 cm depth. While surface specific yield (Sy) values were similar across all sites, it decreased with depth at a rate of 0.014 cm−1 in hollows and 0.007 cm−1 in hummocks. Bulk density (ρb) exhibited similar depth‐dependent trends as Sy and explains a high amount of variance (r2 > 0.69) in moisture retention across a range of pore water pressures (−15 to −500 cm H2O). Because of higher ρb, hollow peat had greater moisture retention, where site effects were minimal. However, the estimated residual water content for surface Sphagnum samples, while on average lower in hummocks (0.082 m3 m−3) versus hollows (0.087 m3 m−3), increased from WET (0.058 m3 m−3) to INT (0.088 m3 m−3) to DRY (0.108 m3 m−3) which has important implications for moisture stress under conditions of persistent WT drawdown. Given the potential importance of microtopographic succession for altering peatland hydraulic structure, our findings point to the need for a better understanding of what controls the relative height and proportional coverage of hummocks in relation to long‐term disturbance‐response dynamics. Copyright © 2014 John Wiley & Sons, Ltd.